2008
DOI: 10.1109/taes.2008.4516999
|View full text |Cite
|
Sign up to set email alerts
|

Directed subspace search ML-PDA with application to active sonar tracking

Abstract: The Maximum Likelihood Probabilistic Data Association (ML-PDA) tracking algorithm is effective in tracking Very Low Observable targets (i.e., very low signal-to-noise ratio (SNR) targets in a high false alarm environment). However, the computational complexity associated with obtaining the track estimate in many cases has precluded its use in real-time scenarios. Previous ML-PDA implementations used a multi-pass grid search to find the track estimate. In this paper, two alternate methods for finding the track … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Three methods have been used to compute the global maximum of JLLR: multi-pass grid (MPG) search [3,4,9], genetic search (GS) [24] and directed subspace search (DSS) [25]. It has been shown that DSS is the most effective technique when tracking a target at low SNR levels (6 dB) and more computationally efficient than the MPG search [25]. But there still is no guarantee that the resulting JLLR maximum is associated with the targets.…”
Section: Cjml-pda Algorithmmentioning
confidence: 99%
“…Three methods have been used to compute the global maximum of JLLR: multi-pass grid (MPG) search [3,4,9], genetic search (GS) [24] and directed subspace search (DSS) [25]. It has been shown that DSS is the most effective technique when tracking a target at low SNR levels (6 dB) and more computationally efficient than the MPG search [25]. But there still is no guarantee that the resulting JLLR maximum is associated with the targets.…”
Section: Cjml-pda Algorithmmentioning
confidence: 99%
“…In [7] ML-PDA was applied to the problem of low-observable target estimation using electro-optical sensors; also a slidingwindow batch approach for ML-PDA estimation was derived, capable of dealing with temporary disappearance of targets and/or targets with velocities changing over time. ML-PDA was also successfully applied to active sonar tracking in [6], where also an efficient computation of the ML estimate, namely, directed subspace search (DSS), was derived. The use of ML-PDA for early track detection with a radar is discussed in [2].…”
Section: B Related Workmentioning
confidence: 99%
“…The transition between the states depends on the PRF, and on the motion. Each "legal" transition between states at time instance m, can be defined by a branch matrix between objects k, and l, at instance time m can be defined similar to [33], to maximize the likelihood ratio of…”
Section: ) Sequential Mle Approximationmentioning
confidence: 99%
“…Solution to the criterion in (9) is complex [33]. A sub-optimal solution, without the need to know the exact probability function of the object properties like in [36], would be to associate to each target or clutter its related objects separately based on the a-priori knowledge about the target properties, and then, in a later processing stage, exclude estimation errors from the targets estimations.…”
Section: B Grouping Objects To Clustersmentioning
confidence: 99%